2019
DOI: 10.1017/wet.2019.64
|View full text |Cite
|
Sign up to set email alerts
|

Management of pigweed (Amaranthusspp.) in grain sorghum with integrated strategies

Abstract: Pigweed is difficult to manage in grain sorghum because of widespread herbicide resistance, a limited number of registered effective herbicides, and the synchronous emergence of pigweed with grain sorghum in Kansas. The combination of cultural and mechanical control tactics with an herbicide program are commonly recognized as best management strategies; however, limited information is available to adapt these strategies to dryland systems. Our objective for this research was to assess the influence of four com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Additionally, waterhemp under 99% shade had mortalities of 97% and 84%, respectively, in May and June. Hay et al (2019) reported that appropriate herbicide strategies resulted in 97% control of Amaranthus species in Kansas grain sorghum [Sorghum bicolor (L.) Moench] across six site-years, while a winter wheat cover crop provided only a 50 percentage point reduction in pigweed density and biomass at three out of six site-years. Similar results were found in this study, as one of the two sites with established cover crops had reductions of 45 percentage points when a cereal rye cover crop was utilized compared to the control treatment.…”
Section: Cover Crop and Weed Biomass Prior To Cover Crop Terminationmentioning
confidence: 99%
“…Additionally, waterhemp under 99% shade had mortalities of 97% and 84%, respectively, in May and June. Hay et al (2019) reported that appropriate herbicide strategies resulted in 97% control of Amaranthus species in Kansas grain sorghum [Sorghum bicolor (L.) Moench] across six site-years, while a winter wheat cover crop provided only a 50 percentage point reduction in pigweed density and biomass at three out of six site-years. Similar results were found in this study, as one of the two sites with established cover crops had reductions of 45 percentage points when a cereal rye cover crop was utilized compared to the control treatment.…”
Section: Cover Crop and Weed Biomass Prior To Cover Crop Terminationmentioning
confidence: 99%